The Effect of Sales Growth and Interest Expense on Financial Health - Saputra, Riyan; Dewi, Intan Pramesti (Dinasti Publisher, 2025)
This research aims to analyze the effect of growth sales and interest expense on financial health. As awareness of the importance of sustainability increases, The financial health of the company is an important indicator in assessing the company's ability to fulfill its short-term and long-term obligations and maintain the stability and continuity of its business. This research uses a quantitative approach with a causal type, utilizing data from in the Consumer Non-Cyclicals sector This research was conducted on companies included in the sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024, the total number of companies that meet the criteria is 114 companies, from the total population, the researcher took a sample of 100 companies using the stratified random sampling technique, which is a random sampling technique by considering the representation of various sub-sectors in the Consumer Non-Cyclicals sector. So this research shows that Growth Sales and Interest Expense have a significant influence on financial health. It is hoped that these findings will provide insight for company management to implement sustainable strategies to maintain financial health stability.